2021
DOI: 10.1177/1049909121989020
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Early Do-Not-Resuscitate Orders Associated With Less Intensive of End-of-Life Care: A Retrospective Cohort Study

Abstract: Background: Dementia is a leading cause of death among US older adults. Little is known about end-of-life care intensity and do-not-resuscitate orders (DNRs) among patients with dementia who die in hospital. Aim: Examine the relationship between dementia, DNR timing, and end-of-life care intensity. Design: Observational cohort study. Setting/Participants: Inpatient electronic health record extraction for 2,566 persons age 65 and older who died in 2 New York City hospitals in the United States from 2015 to 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…An analysis of pre‐2008 Health and Retirement Study data indicated PLWDs were less likely to undergo intensive procedures including mechanical ventilation, intubation, hemodialysis, and CPR at the EOL 3 . Moreover, previous studies are limited in that they only examined selected measures of EOL care intensity, 3,10,12,13 focused on specialized patient populations (e.g., individuals with cancer), 13 or used small samples from limited geographic areas or particular care settings (e.g., nursing homes) 2,4,10 . Finally, dying PLWD also increasingly experience care that promotes their quality of life, including hospice care and home death, 1 These shifts underscore the need to better understand both intensive and comfort‐focused EOL care in this population.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…An analysis of pre‐2008 Health and Retirement Study data indicated PLWDs were less likely to undergo intensive procedures including mechanical ventilation, intubation, hemodialysis, and CPR at the EOL 3 . Moreover, previous studies are limited in that they only examined selected measures of EOL care intensity, 3,10,12,13 focused on specialized patient populations (e.g., individuals with cancer), 13 or used small samples from limited geographic areas or particular care settings (e.g., nursing homes) 2,4,10 . Finally, dying PLWD also increasingly experience care that promotes their quality of life, including hospice care and home death, 1 These shifts underscore the need to better understand both intensive and comfort‐focused EOL care in this population.…”
Section: Introductionmentioning
confidence: 99%
“…3 Moreover, previous studies are limited in that they only examined selected measures of EOL care intensity, 3,10,12,13 focused on specialized patient populations (e.g., individuals with cancer), 13 or used small samples from limited geographic areas or particular care settings (e.g., nursing homes). 2,4,10 Finally, dying PLWD also increasingly experience care that promotes their quality of life, including hospice care and home death, 1 These shifts underscore the need to better understand both intensive and comfort-focused EOL care in this population. Patients often experience both intensive and quality of life-promoting care near the EOL, as evidenced by trends in increased care intensity, hospice use, and days at home.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations